2012
DOI: 10.9790/3008-0213944
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Screening and Antibacterial Studies on Leaf and Root Extracts of Asclepias Curassavica (L).

Abstract: Asclepias curassavica like most of the medicinal plants has highest significance for its valuable secondary metabolites (glycosides and saponins

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Further, it was reported that zone of inhibition is directly proportional to the concentration and highest zone of inhibition was reported from the disc containing highest concentration of extract. The higher activity of ethanolic plant extracts against E. coli, S.aureus and B. subtilis indicates the presence of antimicrobial agents in the tested plants which are useful in curing various skin infections, as these organisms often cause various skin infections in human beings (Reddy et al, 2012). While antifungal assay also suggested the antifungal properties of these plant extracts and it caused reasonable zone of inhibition against the tested fungal cultures (Table 3, Figure 1).…”
Section: Antimicrobial Activitymentioning
confidence: 87%
See 1 more Smart Citation
“…Further, it was reported that zone of inhibition is directly proportional to the concentration and highest zone of inhibition was reported from the disc containing highest concentration of extract. The higher activity of ethanolic plant extracts against E. coli, S.aureus and B. subtilis indicates the presence of antimicrobial agents in the tested plants which are useful in curing various skin infections, as these organisms often cause various skin infections in human beings (Reddy et al, 2012). While antifungal assay also suggested the antifungal properties of these plant extracts and it caused reasonable zone of inhibition against the tested fungal cultures (Table 3, Figure 1).…”
Section: Antimicrobial Activitymentioning
confidence: 87%
“…Phytochemical screening was carried out according to Reddy et al (2012). Different crude extracts collected from Rota evaporator were qualitatively tested for the presence of various phytochemical constituents by using standard methods given by Brain & Turner (1975) and the extractive values were calculated by suggested protocols.…”
Section: Phytochemical Screeningmentioning
confidence: 99%
“…Numerous species of the genus Launaea are used in traditional medicine to treat conditions including stomach ache and skin conditions in addition to offering anticancer, insecticide and cytotoxic properties, effectively preventing CCl4-induced oxidative injuries in the liver and revealing the extract's therapeutic role against bacterial infections as a potent antimicrobial source (Reddy and Mishra, 2012;Khan et al, 2012;Zellagui et al, 2012).…”
Section: The Histological Sections Of the Livers From Female Rats Are...mentioning
confidence: 99%
“…This action may be due to the presence of carbohydrates, carbohydrate derivatives, gums, mucilages, pectin's, various forms of glycosides, tannins, phenolic compounds, lipids, fixed and volatile oils, resins, alkaloids etc. The significance of phytochemical analysis and its importance for the establishment of alternative medicine was expressed 2 . Honey has also been found to be effective in treating bacterial gastroenteritis in infants 3 .…”
Section: Introductionmentioning
confidence: 99%